2005
DOI: 10.2214/ajr.184.1.01840220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Left Gastric Artery as a Route for Catheterization of the Right Gastric Artery

Abstract: The left gastric artery is an appropriate route for selective embolization of the right gastric artery as preparation for long-term hepatic artery infusion chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…They succeeded in selective catheterisation of the right gastric artery using this route in 12 of 14 (86%) patients with smooth anastomoses between the right and left gastric artery. In a later report of embolisation of the right gastric artery using the retrograde approach, embolisation was successful in 79 (89.8%) of 88 patients [33].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They succeeded in selective catheterisation of the right gastric artery using this route in 12 of 14 (86%) patients with smooth anastomoses between the right and left gastric artery. In a later report of embolisation of the right gastric artery using the retrograde approach, embolisation was successful in 79 (89.8%) of 88 patients [33].…”
Section: Discussionmentioning
confidence: 93%
“…Failure to embolise the right gastric artery can result [26]. As an alternative method, a retrograde approach to the right gastric artery via the left gastric artery has been introduced [32,33].…”
mentioning
confidence: 99%
“…Some studies have reported the efficacy of catheter insertion for the RGA via the LGA through the anastomosis when catheterizing the RGA was difficult, and the RGA is then embolized to prevent a gastric ulcer during hepatic arterial infusion chemotherapy [8-10]. Alternatively, to the best of our knowledge, there have been no reports of catheterizing and embolizing the replaced LHA via the RGA through the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the flushing proceeded without any serious problems, such as coil migration or the dislocation or occlusion of a catheter. In applying the system to clinical cases, however, it is necessary to judge whether, for each case, we should select the conventional method using a coil pusher (16) or a saline flush technique (15), because careful manipulation using a coil pusher during the embolization procedure is preferable in some cases. On the other hand, the saline flush technique (15) was used for embolization of larger arterial branches through the larger catheters; flushing microcoils through the microcatheter in the small arterial branch may result in rupture of this branch, and, in some cases, "flushing" may be not possible due to peripheral resistance.…”
Section: Discussionmentioning
confidence: 99%